Development Of A Decision Support System Based On Rule-Based Systems For Determining Marketing Strategies And Superior Products at Tombo Ngelih Cafe - Firdiyastomo, Yogi; Wardani, Setia; Rianto (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2025)
Study This, aiming to develop a system supporting decision-making based on a rule-based system in determining marketing and product strategies, featured in Cafe Tombo Smile. Method used covering data collection through observation, interviews, and studies library, and an implementation system web-based using PHP and MySQL. The test results using ¬ black-box and alpha methods that well-recommended well recommendation,,, marketing and as as product product effective flagship.